Factors Influencing The Use Of The JKN Mobile Application In Rupit District, North Musi Rawas Regency - Zakia Darurahma; Adila Solida; Rumita Ena Sari; Arnild Augina Mekarisce (CV. AFDIFAL MAJU BERKAH, 2026)
The use of digital health services through the Mobile JKN application has become an important part of the transformation of health services in the digital era. However, the use of the Mobile JKN application in the community is still not optimal. This study aims to analyze the relationship between perceived usefulness, perceived ease of use, attitudes toward use, and intention to use with the use of the Mobile JKN application. This study used a quantitative design with a cross-sectional approach. The study population was JKN participants in the Rupit Community Health Center working area with a sample of 96 respondents selected using an accidental sampling technique. The research instrument used a structured questionnaire, while data analysis was carried out using the chi-square test and the calculation of the Prevalence Ratio (PR). The results showed a significant relationship between perceived usefulness (p = 0.045; PR = 2.02), perceived ease of use (p = 0.000; PR = 3.36), attitudes toward use (p = 0.017; PR = 3.31), and intention to use (p = 0.027; PR = 2.14) with the use of the Mobile JKN application. Perceived ease of use was the factor with the greatest risk value for not using the application. The conclusion of this study is that factors in the Technology Acceptance Model are related to the use of the Mobile JKN application, so that increasing ease, benefits, positive attitudes, and usage intentions need to be strengthened to increase sustainable use of the application.